The BGG Complex on Projective Space - Eastwood, M.G.; Gover, A.R. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We give a complete construction of the Bernstein-Gelfand-Gelfand complex on real or complex projective space using minimal ingredients.